Three chemotypes of thyme (Thymus vulgaris L.) essential oil and their main compounds affect differently the IL-6 and TNFα cytokine secretions of BV-2 microglia by modulating the NF-κB and C/EBPβ signalling pathways - Györgyi Horváth; Adrienn Horváth; Gréta Reichert; Andrea Böszörményi; Katalin Sipos; Edina Pandur (BMC, 2021)
Abstract Background The essential oils possess both antimicrobial and anti-inflammatory effects, therefore they can provide an effective treatment against infections. Essential oils are widely used as supportive ingredients in many diseases, especially in the acute and chronic diseases of the respiratory tract. Neuroinflammation is responsible for several diseases of the central nervous system. Some plant-derived bioactive molecules have been shown to have role in attenuating neuroinflammation by regulating microglia, the immune cells of the CNS. Methods In this study, the anti-inflammatory effect of three chemotypes of thyme essential oil and their main compounds (geraniol, thujanol and linalool) were examined on lipopolysaccharide-induced BV-2 microglia. Three different experimental setups were used, LPS pretreatment, essential oil pretreatment and co-treatments of LPS and essential oils in order to determine whether essential oils are able to prevent inflammation and can decrease it. The concentrations of the secreted tumour necrosis factor α (TNFα) and interleukin-6 (IL-6) proinflammatory cytokines were measured and we analysed by Western blot the activity of the cell signalling pathways, NF-κB and CCAAT-enhancer binding protein β (C/EBPβ) regulating TNFα and IL-6 proinflammatory cytokine expressions in BV-2 cells. Results Our results showed definite alterations in the effects of essential oil chemotypes and their main compounds at the different experimental setups. Considering the changes of IL-6 and TNFα secretions the best reduction of inflammatory cytokines could be reached by the pretreatment with the essential oils. In addition, the main compounds exerted better effects than essential oil chemotypes in case of LPS pretreatment. At the essential oil pretreatment experiment, the effect of linalool and geraniol was outstanding but there was no major difference between the actions of chemotypes and standards. Main compounds could be seen to have large inhibitory effects on certain cell signalling components related to the activation of the expression of proinflammatory cytokines. Conclusion Thyme essential oils are good candidates to use in prevention of neuroinflammation and related neurodegeneration, but the exact ratio of the components has to be selected carefully.